Iron Deficiency Is Common after Restorative Proctocolectomy with Ileal Pouch-Anal Anastomosis in Patients with Ulcerative Colitis - Ishaan Dharia; Taqwa Ahmed; Michael Plietz; Sergey Khaitov; Patricia Sylla; Alexander Greenstein; Marla C. Dubinsky; Maia Kayal (Inflammatory Intestinal Diseases, 2023)
Background: Micronutrient deficiencies may occur after restorative proctocolectomy (RPC) with ileal pouch-anal anastomosis (IPAA) in patients with ulcerative colitis (UC), largely due to malabsorption and/or pouch inflammation. Objectives: The objective of this study was to report the frequency of iron deficiency in patients with UC who underwent RPC with IPAA and identify associated risk factors. Methods: We conducted a retrospective chart review of patients with UC or IBD-unclassified who underwent RPC with IPAA at Mount Sinai Hospital between 2008 and 2017. Patients younger than 18 years of age at the time of colectomy were excluded. Descriptive statistics were used to analyze baseline characteristics. Medians with interquartile range (IQR) were reported for continuous variables, and proportions were reported for categorical variables. Iron deficiency was defined by ferritin <30 ng/mL. Logistic regression was used to analyze unadjusted relationships between hypothesized risk factors and the outcome of iron deficiency. Results: A total of 143 patients had iron studies a median of 3.0 (IQR 1.7–5.6) years after final surgical stage, of whom 73 (51.0%) were men. The median age was 33.5 (IQR 22.7–44.3) years. Iron deficiency was diagnosed in 80 (55.9%) patients with a median hemoglobin of 12.4 g/dL (IQR 10.9–13.3), ferritin of 14 ng/mL (IQR 9.0–23.3), and iron value of 44 μg/dL (IQR 26.0–68.8). Of these, 29 (36.3%) had a pouchoscopy performed within 3 months of iron deficiency diagnosis. Pouchitis and cuffitis were separately noted in 4 (13.8%) and 13 (44.8%) patients, respectively, and concomitant pouchitis-cuffitis was noted in 9 (31.0%) patients. Age, sex, anastomosis type, pouch duration, and history of pouchitis and/or cuffitis were not associated with iron deficiency. Conclusion: Iron deficiency is common after RPC with IPAA in patients with UC. Cuffitis is seen in the majority of patients with iron deficiency; however, iron deficiency may occur even in the absence of inflammation.